Highly heat-resistant and corrosion-resistant stainless steel solid welding wire and preparation method and application thereof
By developing the stainless steel solid gas -saving welding wires composed of alloy elements such as CR, Ni, MN, SI, the problem of lack of high temperature and corrosion resistance of magnesium equipment at high temperatures at high temperatures, and achieve higher welding efficiency and equipment and equipment Life life.
Patent Information
- Application Number
- CN202310576960.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-05-22
AI Technical Summary
The existing welding materials used in magnesium industry equipment have problems such as low melting efficiency, poor high temperature durability and sulfur corrosion resistance at high temperatures, resulting in a shortening of the service life of the equipment.
Develop a stainless steel solid gas -saving welding wire composed of alloy elements such as CR, Ni, MN, SI. By optimizing chemical composition and manufacturing process, welding efficiency and high temperature resistance are improved.
The welding efficiency and process performance were improved, the service life of the magnesium industry was extended, the cost was reduced, and the anti -high temperature oxidation and high temperature sulfur corrosion capacity of the welded joint was significantly improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of welding material preparation, and in particular relates to a solid welding wire for stainless steel resistant to high temperature corrosion, and a preparation method and application thereof. Technical Background
[0002] High temperature resistant stainless steel materials are widely used in the fields of petroleum, chemical industry, nuclear power, etc., especially in the magnesium smelting industry. With the development of materials science, the demand for magnesium metal has increased rapidly at home and abroad. The magnesium smelting industry has also developed rapidly, and the life requirements for core equipment for reducing magnesium have also increased accordingly. In order to improve equipment manufacturing efficiency and extend equipment life, the industry has also put forward higher requirements for its welding materials.
[0003] CN104259690A (201410324472.2, Beijing University of Technology) discloses a stainless heat-resistant self-shielded flux-cored welding wire for magnesium smelting reduction tank, which uses a common stainless steel strip 304L as a coating layer; the mass percentages of the alloy components in the powder core are: the mass percentage of rutile is 8-16%, the mass percentage of sodium carbonate is 0.6-2.3%, the mass percentage of feldspar is 3-8%, the mass percentage of complex fluoride is 6-12%, the mass percentage of chromium is 15-35%, the mass percentage of nickel is 8-15%, the mass percentage of manganese is 2-5%, and the mass percentage of molybdenum is 3-10% The mass percentage of chromium nitride is 1-6%, the mass percentage of aluminum-magnesium alloy is 4-6%, the mass percentage of mixed rare earth is 3-7%, and the mass percentage of reduced iron powder is 0-11.2%; the mass percentage of the components of the mixed rare earth is: La2O3: 25-32%, CeO2: 45-50%, Pr2O3: 4-6%, Nd2O3: 14-20%; the mass ratio of Al:Mg in the aluminum-magnesium alloy is 1:1, and the filling rate of the welding wire is 15-35%; the mass percentage of each fluoride in the composite fluoride is 20%BaF2-8%LiF2-10%MgF2-62CaF2. It is believed that compared with the currently used stainless steel electrodes, the present invention can use a larger welding current, a faster welding speed, improve production efficiency, and reduce labor intensity; compared with the currently used stainless steel submerged arc welding solid wire, it can be welded in all positions, has a small heat input, good slag removal, and a simpler manufacturing process; compared with the performance of joints welded by stainless steel electrodes and stainless steel solid wires, it has better thermal strength, oxidation resistance, sulfide corrosion resistance and high temperature creep resistance.
[0004] CN105880867A (201410448397.0, Illinois) discloses a flux-cored welding wire, the flux-cored welding wire includes a shell, the shell is provided with a lumen, the lumen contains a flux core, the stainless steel used to make the shell is austenitic stainless steel. The flux core contains, by weight percentage: 2%-10% of powder containing SiO2; 2%-8% of potassium titanate; 20%-35% of powder containing TiO2; 5%-15% of manganese powder; 0-4% of nickel powder; 0-4% of aluminum-magnesium alloy; 0-4% of fluoride; 35%-50% of metallic chromium; 0.5-4% of chromium nitride; 0-4% of Al2O3; 0-4% of ZrO2; 0-2% of Bi2O3; the weight content of SiO2 in the powder containing SiO2 is more than 90%. It is believed that the invention provides a CO2 gas shielded flux-cored welding wire with a material similar to that of a magnesium reduction tank, which has high welding efficiency, good operability, good arc stiffness, small spatter, and can be welded in all positions.
[0005] CN112975208A (202110310637.0, Beijing University of Technology) discloses a metal core welding wire for submerged arc welding of heat-resistant stainless steel in magnesium reduction tanks, which belongs to the field of material processing engineering and is mainly used for welding heat-resistant steel in magnesium reduction tanks. The metal core welding wire uses 304L stainless steel strip as a coating layer, and the mass percentage of each alloy component in the powder core is: the mass percentage of metal chromium powder is 15-26%, the mass percentage of high carbon ferrochrome is 10-20%, the mass percentage of metal nickel powder is 15-29%, the mass percentage of electrolytic manganese is 3-6%, the mass percentage of molybdenum iron (Mo% = 60%) is 10-20%, the mass percentage of ferrochrome nitride is 5-10%, the mass percentage of aluminum-magnesium alloy is 1-3%, the mass percentage of rare earth ferrosilicon is 1-3%, the mass percentage of mixed rare earth is 2-8%, and the remainder is reduced iron powder. Among them, Mo% in ferromolybdenum is 60%; the composition of mixed rare earth is: La2O3: 32%, CeO2: 45-50%, Pr2O3: 4-6%, Nd2O3: 14-17%; the filling rate of the metal core welding wire is 40-45%, and the diameter of the welding wire is 3.2-4.0mm. When the metal core welding wire is used for welding, the welding method is submerged arc welding, the flux brand used is sintered flux 101, the welding current range of the welding wire is 350-600A, and the welding voltage range is 35-45V. The stainless steel metal core welding wire is made of 304L stainless steel strip, the width of the 304L steel strip is 14-16mm, the thickness is 0.4mm, and the chemical composition range of the deposited metal includes the following (mass percentage): C: 0.3-0.8%, : 24-28%, Ni: 7-17%, Si: 0.5-1.5%, Mn: 0.6-1.5%, Mo: 2.5-4.5%, N: 0.2-0.3%, S: ≤0.030%, P: ≤0.030%, Re: 0.3-1.0%, and the balance is Fe. It is believed that the weld of the invention has beautiful shape, and the welded joint has excellent mechanical properties and high temperature resistance.
[0006] CN114515919A (202210229004.1, Xuli Electromechanical) discloses a high Cr and low Ni flux-cored welding wire for magnesium reduction tank and its preparation method and application. The flux-cored welding wire includes powder and welding skin, wherein the powder includes the following components by mass percentage: Si powder 1.0-1.5%, Mn powder 8.0-10.0%, Cr powder 40.0-50.0%, Ni powder 12.0-15.0%, Nb powder 3.0-4.0%, Ti powder 1.0-1.5%, Al powder 0.8-1.0%, graphene 0.1-0.3%, and the rest is Fe powder, and the sum of the mass percentages of the above components is 100%. The preparation method is: the above alloy powder is mixed and dried, and then wrapped with 0Cr19Ni10 strip and drawn. It is believed that the flux-cored welding wire of the invention is used for welding magnesium reduction tank, and the obtained head has high strength and good toughness, and no defects are produced in the weld.
[0007] CN101362260B (200810223090.5, Jinwei) discloses a special stainless steel welding rod for magnesium reduction tank, which is made by mixing the following powder raw materials and adding 2.8M, 48°Be potassium sodium water glass which accounts for 25% of the total weight of the powder raw materials, stirring evenly, and pressing and coating on the stainless steel welding core: the weight proportion of the powder raw materials: marble 43-52 parts; fluorite 16-23 parts; titanium dioxide 1-3 parts; quartz 1-3 parts; mica 1-3 parts; ferrosilicon 4-6 parts; ferrotitanium 3-5 parts; ferromanganese 4-6 8-12 parts of ferrochrome; 1-3 parts of calcium solvent; 1-3 parts of soda ash; 8-12 parts of ferrochrome nitride; the calcium solvent is a mineral compound of calcium, which is composed of 50% calcium carbonate and 50% calcium oxide; the chemical composition of the welding core of the stainless steel welding rod is as follows: C≤0.15, Si≤0.35, Mn: 1.0-2.5, P≤0.03, S≤0.015, Ni: 8.0-10.0, Cr: 25.0-28.0, Mo≤0.75, Cu≤0.75, and the rest is Fe. It is believed that the welding rod of the invention has strong oxidation resistance, sulfide resistance, and corrosion resistance, and has good crack resistance; high welding efficiency; large arc blowing force and good welding performance; the medicine skin is not easy to turn red and crack during welding, the remaining part of the welding rod is short, and it is easy to remove slag in deep and narrow grooves, no special equipment is required, and the cost is low; but the service life of the post-weld reduction tank is generally only 80 to 85 days.
[0008] As we all know, the core equipment used for reducing magnesium usually needs to withstand the erosion of high temperature of 1200℃ and high temperature gas medium. At present, the welding materials used for such magnesium industry equipment in China have disadvantages such as low deposition efficiency, relatively poor high temperature durability and sulfide corrosion resistance. During the use of the equipment, there is a phenomenon that the matrix is intact but the weld has been corroded. Therefore, the development of a new type of high temperature corrosion resistant solid gas shielded welding wire, improving welding efficiency, optimizing welding process, extending the service life of the core equipment for reducing magnesium, reducing costs, and creating better economic benefits is still eagerly expected by those skilled in the art. Summary of the invention
[0009] The purpose of the present invention is to develop a new type of solid gas shielded welding wire to meet the welding requirements of magnesium industry equipment, improve welding efficiency, optimize welding technology, extend the service life of core equipment for reducing magnesium, reduce costs, and create better economic benefits. To this end, the present invention provides a stainless steel gas shielded welding wire composed of alloy elements such as Cr, Ni, Mn, and Si to overcome the shortcomings of the prior art.
[0010] To this end, the first aspect of the present invention provides a stainless steel solid welding wire, characterized in that its chemical composition mass percentage is: C: 0.05% ~ 0.3%, Mn: 1.0% ~ 3.0%, Si: 0.20 ~ 0.70, P ≤ 0.030%, S ≤ 0.015%, Cr: 21% ~ 25%, Ni: 7.0% ~ 10.0%, Mo ≤ 0.15%, Cu ≤ 0.25%, N: 0.08% ~ 0.30%, V: 0.050% ~ 0.100%, W: 0.020% ~ 0.060%, B: 0.010% ~ 0.020%, Ti: 0.02% ~ 0.05%, RE: 0.002 ~ 0.006%, and the rest is Fe and other inevitable impurities.
[0011] The stainless steel solid welding wire according to the first aspect of the present invention is characterized in that its chemical composition mass percentage is: C: 0.06% ~ 0.28%, Mn: 1.2% ~ 2.9%, Si: 0.29% ~ 0.63%, P: 0.019% ~ 0.026%, S: 0.008% ~ 0.012%, Cr: 21.9% ~ 24.8%, Ni: 7.3% ~ 9.6%, Mo: 0.07% ~ 0.14%, Cu: 0.11% ~ 0.13%, N: 0.09% ~ 0.27%, V: 0.054% ~ 0.084%, W: 0.023% ~ 0.056%, B: 0.012% ~ 0.019%, Ti: 0.029% ~ 0.046%, RE: 0.003% ~ 0.005%, and the rest is Fe and other inevitable impurities.
[0012] The stainless steel solid welding wire according to the first aspect of the present invention is characterized in that its chemical composition mass percentage is: C: 0.06%, Mn: 2.5%, Si: 0.53%, P: 0.023%, S: 0.009%, Cr: 22.5%, Ni: 7.3%, Mo: 0.13%, Cu: 0.13%, N: 0.13%, V: 0.054%, W: 0.045%, B: 0.012%, Ti: 0.031%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.005%, and the rest is Fe and other inevitable impurities.
[0013] The stainless steel solid welding wire according to the first aspect of the present invention is characterized in that its chemical composition mass percentage is: C: 0.10%, Mn: 1.2%, Si: 0.36%, P: 0.019%, S: 0.012%, Cr: 23.9%, Ni: 7.9%, Mo: 0.11%, Cu: 0.12%, N: 0.09%, V: 0.073%, W: 0.049%, B: 0.014%, Ti: 0.029%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.004%, and the rest is Fe and other inevitable impurities.
[0014] The stainless steel solid welding wire according to the first aspect of the present invention is characterized in that its chemical composition mass percentage is: C: 0.24%, Mn: 2.9%, Si: 0.63%, P: 0.026%, S: 0.011%, Cr: 21.9%, Ni: 8.5%, Mo: 0.07%, Cu: 0.12%, N: 0.22%, V: 0.064%, W: 0.023%, B: 0.019%, Ti: 0.046%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.005%, and the rest is Fe and other inevitable impurities.
[0015] The stainless steel solid welding wire according to the first aspect of the present invention is characterized in that its chemical composition mass percentage is: C: 0.28%, Mn: 1.6%, Si: 0.29%, P: 0.021%, S: 0.008%, Cr: 24.8%, Ni: 8.8%, Mo: 0.09%, Cu: 0.11%, N: 0.27%, V: 0.082%, W: 0.037%, B: 0.016%, Ti: 0.031%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.003%, and the rest is Fe and other inevitable impurities.
[0016] The stainless steel solid welding wire according to the first aspect of the present invention is characterized in that its chemical composition mass percentage is: C: 0.17%, Mn: 2.2%, Si: 0.44%, P: 0.019%, S: 0.009%, Cr: 23.3%, Ni: 9.6%, Mo: 0.14%, Cu: 0.13%, N: 0.17%, V: 0.084%, W: 0.056%, B: 0.015%, Ti: 0.034%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.004%, and the rest is Fe and other inevitable impurities.
[0017] According to the first aspect of the present invention, the stainless steel solid welding wire is characterized in that it uses a metal arc welding method (e.g., a current of 120-160A, a shielding gas of 80% Ar+20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.05% ~ 0.3%, Mn: 1.0% ~ 3.0%, Si: 0.20 ~ 0.70, P ≤ 0.030%, S ≤ 0.015%, Cr: 21% ~ 25%, Ni: 7.0% ~ 10.0%, Mo ≤ 0.15%, Cu ≤ 0.25%, N: 0.08% ~ 0.30%, V: 0.050% ~ 0.100%, W: 0.020% ~ 0.060%, B: 0.010% ~ 0.020%, Ti: 0.02% ~ 0.05%, RE: 0.002% ~ 0.006%, and the rest are Fe and other inevitable impurities.
[0018] According to the first aspect of the present invention, the stainless steel solid welding wire is characterized in that it uses metal arc welding (for example, current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition mass percentage of the deposited metal is as follows: C: 0.05% ~ 0.25%, Mn: 1.1% ~ 2.5%, Si: 0.26% ~ 0.52%, P: 0.018% ~ 0.025%, S: 0.007% ~ 0.013%, Cr: 21.1% ~ 24.2%, Ni: 7.2% ~ 9.3%, Mo: 0.06% ~ 0.12%, Cu: 0.11% ~ 0.12%, N: 0.08% ~ 0.26%, V: 0.049% ~ 0.076%, W: 0.021% ~ 0.053%, B: 0.011% ~ 0.017%, Ti: 0.020% ~ 0.042%, RE: 0.002% ~ 0.004%, and the rest are Fe and other inevitable impurities.
[0019] According to the first aspect of the present invention, the stainless steel solid welding wire is characterized in that it uses metal arc welding (for example, current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.05%, Mn: 2.4%, Si: 0.51%, P: 0.024%, S: 0.010%, Cr: 22.1%, Ni: 7.2%, Mo: 0.11%, Cu: 0.12%, N: 0.10%, V: 0.049%, W: 0.043%, B: 0.011%, Ti: 0.023%, RE: 0.004%, and the rest are Fe and other inevitable impurities.
[0020] According to the first aspect of the present invention, the stainless steel solid welding wire is characterized in that it uses metal arc welding (for example, current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.09%, Mn: 1.1%, Si: 0.30%, P: 0.019%, S: 0.013%, Cr: 23.5%, Ni: 7.5%, Mo: 0.10%, Cu: 0.12%, N: 0.08%, V: 0.067%, W: 0.048%, B: 0.013%, Ti: 0.020%, RE: 0.003%, and the rest are Fe and other inevitable impurities.
[0021] According to the first aspect of the present invention, the stainless steel solid welding wire is characterized in that it uses metal arc welding (for example, current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.23%, Mn: 2.5%, Si: 0.52%, P: 0.025%, S: 0.010%, Cr: 21.1%, Ni: 8.3%, Mo: 0.06%, Cu: 0.12%, N: 0.21%, V: 0.059%, W: 0.021%, B: 0.017%, Ti: 0.042%, RE: 0.004%, and the rest are Fe and other inevitable impurities.
[0022] According to the first aspect of the present invention, the stainless steel solid welding wire is characterized in that it uses metal arc welding (for example, current 120-160A, shielding gas 80% Ar + 20% CO 2The welding was carried out under the conditions of (a) , and the chemical composition mass percentage of the deposited metal was: C: 0.25%, Mn: 1.4%, Si: 0.26%, P: 0.021%, S: 0.007%, Cr: 24.2%, Ni: 8.3%, Mo: 0.07%, Cu: 0.11%, N: 0.26%, V: 0.076%, W: 0.033%, B: 0.013%, Ti: 0.025%, RE: 0.002%, and the rest were Fe and other inevitable impurities.
[0023] According to the first aspect of the present invention, the stainless steel solid welding wire is characterized in that it uses metal arc welding (for example, current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.12%, Mn: 2.0%, Si: 0.37%, P: 0.018%, S: 0.009%, Cr: 23.0%, Ni: 9.3%, Mo: 0.12%, Cu: 0.11%, N: 0.14%, V: 0.074%, W: 0.053%, B: 0.013%, Ti: 0.031%, RE: 0.003%, and the rest are Fe and other inevitable impurities.
[0024] According to the first aspect of the present invention, the stainless steel solid welding wire is characterized in that the RE, i.e., mixed rare earth, is a mixed rare earth with La:Ce:Nd in a weight ratio of 2:5:1.
[0025] The stainless steel solid welding wire according to the first aspect of the present invention is characterized in that it is prepared according to the following method: desulfurized molten iron converter is used for steelmaking, raw materials such as electrolytic manganese, ferrosilicon, chromium nitride, metallic nickel, metallic molybdenum, copper powder, ferrovanadium, ferrotungsten, borax, potassium titanate, mixed rare earth and pure iron are added in proportion during the smelting process, and the top and bottom composite blowing process is used to smelt until carbon, sulfur and phosphorus are controlled at specified levels, after deoxidation and alloying, the LF furnace is used for refining outside the furnace to adjust some trace elements and smelt molten steel with the required composition, the molten steel is cast into continuous casting billet by casting equipment, and then rolled into wire rod with Φ=4~7mm, and then the wire rod is drawn into finished welding wire with Φ=0.5~2.5mm.
[0026] Further, the second aspect of the present invention provides a method for preparing a solid stainless steel welding wire, wherein the chemical composition mass percentage of the solid stainless steel welding wire is: C: 0.05% to 0.3%, Mn: 1.0% to 3.0%, Si: 0.20 to 0.70, P≤0.030%, S≤0.015%, Cr: 21% to 25%, Ni: 7.0% to 10.0%, Mo≤0.15%, Cu≤0.25%, N: 0.08% to 0.30%, V: 0.050% to 0.100%, W: 0.020% to 0.060%, B: 0.010% to 0.020%, Ti: 0.02% to 0.05%, RE: 0.002% to 0.006% 6%, and the rest is Fe and other inevitable impurities; the method comprises the following steps: it is prepared according to the following method: using desulfurized molten iron converter to make steel, adding raw materials electrolytic manganese, ferrosilicon, chromium nitride, metallic nickel, metallic molybdenum, copper powder, ferrovanadium, ferrotungsten, borax, potassium titanate, mixed rare earth, pure iron in proportion during the smelting process, adopting top and bottom composite blowing process to smelt until carbon, sulfur and phosphorus are controlled at the specified level, after deoxidation and alloying, adopting LF furnace out-of-furnace refining process to adjust some trace elements, smelting molten steel with composition meeting the requirements, casting the molten steel into continuous casting billet through casting equipment, and then rolling it into wire rod with Φ=4-7mm, and then drawing the wire rod into finished welding wire with Φ=0.5-2.5mm.
[0027] According to the method of the second aspect of the present invention, the chemical composition mass percentage of the stainless steel solid welding wire is: C: 0.06% ~ 0.28%, Mn: 1.2% ~ 2.9%, Si: 0.29% ~ 0.63%, P: 0.019% ~ 0.026%, S: 0.008% ~ 0.012%, Cr: 21.9% ~ 24.8%, Ni: 7.3% ~ 9.6%, Mo: 0.07% ~ 0.14%, Cu: 0.11% ~ 0.13%, N: 0.09% ~ 0.27%, V: 0.054% ~ 0.084%, W: 0.023% ~ 0.056%, B: 0.012% ~ 0.019%, Ti: 0.029% ~ 0.046%, RE: 0.003% ~ 0.005%, and the rest is Fe and other inevitable impurities.
[0028] According to the method of the second aspect of the present invention, the chemical composition mass percentage of the stainless steel solid welding wire is: C: 0.06%, Mn: 2.5%, Si: 0.53%, P: 0.023%, S: 0.009%, Cr: 22.5%, Ni: 7.3%, Mo: 0.13%, Cu: 0.13%, N: 0.13%, V: 0.054%, W: 0.045%, B: 0.012%, Ti: 0.031%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.005%, and the rest is Fe and other inevitable impurities.
[0029] According to the method of the second aspect of the present invention, the chemical composition mass percentage of the stainless steel solid welding wire is: C: 0.10%, Mn: 1.2%, Si: 0.36%, P: 0.019%, S: 0.012%, Cr: 23.9%, Ni: 7.9%, Mo: 0.11%, Cu: 0.12%, N: 0.09%, V: 0.073%, W: 0.049%, B: 0.014%, Ti: 0.029%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.004%, and the rest is Fe and other inevitable impurities.
[0030] According to the method of the second aspect of the present invention, the chemical composition mass percentage of the stainless steel solid welding wire is: C: 0.24%, Mn: 2.9%, Si: 0.63%, P: 0.026%, S: 0.011%, Cr: 21.9%, Ni: 8.5%, Mo: 0.07%, Cu: 0.12%, N: 0.22%, V: 0.064%, W: 0.023%, B: 0.019%, Ti: 0.046%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.005%, and the rest is Fe and other inevitable impurities.
[0031] According to the method of the second aspect of the present invention, the chemical composition mass percentage of the stainless steel solid welding wire is: C: 0.28%, Mn: 1.6%, Si: 0.29%, P: 0.021%, S: 0.008%, Cr: 24.8%, Ni: 8.8%, Mo: 0.09%, Cu: 0.11%, N: 0.27%, V: 0.082%, W: 0.037%, B: 0.016%, Ti: 0.031%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.003%, and the rest is Fe and other inevitable impurities.
[0032] According to the method of the second aspect of the present invention, the chemical composition mass percentage of the stainless steel solid welding wire is: C: 0.17%, Mn: 2.2%, Si: 0.44%, P: 0.019%, S: 0.009%, Cr: 23.3%, Ni: 9.6%, Mo: 0.14%, Cu: 0.13%, N: 0.17%, V: 0.084%, W: 0.056%, B: 0.015%, Ti: 0.034%, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.004%, and the rest is Fe and other inevitable impurities.
[0033] According to the method of the second aspect of the present invention, the stainless steel solid welding wire is welded by metal arc welding (e.g., current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.05% ~ 0.3%, Mn: 1.0% ~ 3.0%, Si: 0.20 ~ 0.70, P ≤ 0.030%, S ≤ 0.015%, Cr: 21% ~ 25%, Ni: 7.0% ~ 10.0%, Mo ≤ 0.15%, Cu ≤ 0.25%, N: 0.08% ~ 0.30%, V: 0.050% ~ 0.100%, W: 0.020% ~ 0.060%, B: 0.010% ~ 0.020%, Ti: 0.02% ~ 0.05%, RE: 0.002% ~ 0.006%, and the rest are Fe and other inevitable impurities.
[0034] According to the method of the second aspect of the present invention, the stainless steel solid welding wire is welded by metal arc welding (e.g., current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition mass percentage of the deposited metal is as follows: C: 0.05% ~ 0.25%, Mn: 1.1% ~ 2.5%, Si: 0.26% ~ 0.52%, P: 0.018% ~ 0.025%, S: 0.007% ~ 0.013%, Cr: 21.1% ~ 24.2%, Ni: 7.2% ~ 9.3%, Mo: 0.06% ~ 0.12%, Cu: 0.11% ~ 0.12%, N: 0.08% ~ 0.26%, V: 0.049% ~ 0.076%, W: 0.021% ~ 0.053%, B: 0.011% ~ 0.017%, Ti: 0.020% ~ 0.042%, RE: 0.002% ~ 0.004%, and the rest are Fe and other inevitable impurities.
[0035] According to the method of the second aspect of the present invention, the stainless steel solid welding wire is welded by metal arc welding (e.g., current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.05%, Mn: 2.4%, Si: 0.51%, P: 0.024%, S: 0.010%, Cr: 22.1%, Ni: 7.2%, Mo: 0.11%, Cu: 0.12%, N: 0.10%, V: 0.049%, W: 0.043%, B: 0.011%, Ti: 0.023%, RE: 0.004%, and the rest are Fe and other inevitable impurities.
[0036] According to the method of the second aspect of the present invention, the stainless steel solid welding wire is welded by metal arc welding (e.g., current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.09%, Mn: 1.1%, Si: 0.30%, P: 0.019%, S: 0.013%, Cr: 23.5%, Ni: 7.5%, Mo: 0.10%, Cu: 0.12%, N: 0.08%, V: 0.067%, W: 0.048%, B: 0.013%, Ti: 0.020%, RE: 0.003%, and the rest are Fe and other inevitable impurities.
[0037] According to the method of the second aspect of the present invention, the stainless steel solid welding wire is welded by metal arc welding (e.g., current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.23%, Mn: 2.5%, Si: 0.52%, P: 0.025%, S: 0.010%, Cr: 21.1%, Ni: 8.3%, Mo: 0.06%, Cu: 0.12%, N: 0.21%, V: 0.059%, W: 0.021%, B: 0.017%, Ti: 0.042%, RE: 0.004%, and the rest are Fe and other inevitable impurities.
[0038] According to the method of the second aspect of the present invention, the stainless steel solid welding wire is welded by metal arc welding (e.g., current 120-160A, shielding gas 80% Ar + 20% CO 2The welding was carried out under the conditions of (a) , and the chemical composition mass percentage of the deposited metal was: C: 0.25%, Mn: 1.4%, Si: 0.26%, P: 0.021%, S: 0.007%, Cr: 24.2%, Ni: 8.3%, Mo: 0.07%, Cu: 0.11%, N: 0.26%, V: 0.076%, W: 0.033%, B: 0.013%, Ti: 0.025%, RE: 0.002%, and the rest were Fe and other inevitable impurities.
[0039] According to the method of the second aspect of the present invention, the stainless steel solid welding wire is welded by metal arc welding (e.g., current 120-160A, shielding gas 80% Ar + 20% CO 2 The chemical composition of the deposited metal is as follows: C: 0.12%, Mn: 2.0%, Si: 0.37%, P: 0.018%, S: 0.009%, Cr: 23.0%, Ni: 9.3%, Mo: 0.12%, Cu: 0.11%, N: 0.14%, V: 0.074%, W: 0.053%, B: 0.013%, Ti: 0.031%, RE: 0.003%, and the rest are Fe and other inevitable impurities.
[0040] According to the method of the second aspect of the present invention, the RE, i.e., mixed rare earth, is a mixed rare earth with La:Ce:Nd in a weight ratio of 2:5:1.
[0041] Those skilled in the art know that some chemical compositions in the welding wire of the present invention generally have the following properties.
[0042] C: The appropriate increase of carbon element can play a role in solid solution strengthening on the one hand, and can form a second phase on the other hand, which can significantly improve the high temperature creep strength and fracture strength of the deposited metal. Too high will affect the welding process performance of the welding wire and have an adverse effect on the toughness of the weld metal, so the carbon element is controlled in the range of 0.05%-0.3%.
[0043] Mn: Mn is an austenite forming element. Mn preferentially combines with S to form high melting point MnS, which reduces the tendency of S to form a low melting point eutectic liquid film, weakens the harmful effects of S, reduces the tendency of crystallization cracks, and improves the crack resistance of the deposited metal. It can also improve the solid solubility of nitrogen, making the drawn wire welding process stable and improving the welding process performance.
[0044] Mo: Mo plays a role in solid solution strengthening and improves the high temperature performance of the weld, but too high a content will lead to carbides at the austenite grain boundaries and deteriorate the toughness of the weld.
[0045] Si: Si is a ferrite-forming element and has a deoxidizing effect, but if the content is too high, it will form a low-melting-point eutectic with impurity elements, which is prone to thermal cracking.
[0046] Cr: Cr can form a dense oxide film on the surface of steel to prevent further oxidation. It is the main element used to improve the oxidation resistance of heat-resistant steel.
[0047] Ni: Ni is the main element for forming austenite, which can improve the stability of austenite. It can strengthen the solid solution with elements such as Mo, increase the bonding force between atoms and improve the strength of the matrix.
[0048] N: N is a strong austenite-forming element. On the one hand, it can replace the expensive metal Ni and stabilize the austenite matrix. On the other hand, it combines with other elements to form nitrides that precipitate on the grain boundaries, which can improve the high-temperature strength of the grain boundaries and thus enhance the high-temperature creep strength of the weld.
[0049] S, P: impurity elements, should be controlled as much as possible. Too high phosphorus will deteriorate the low temperature performance of the material, and sulfur will deteriorate the thermal cracking resistance of the material.
[0050] V: It can refine the grain size and improve the matrix strength.
[0051] B: Trace amounts of boron can increase intergranular strength, thereby improving the strength and toughness of the material.
[0052] RE (mixed rare earth): The cleanliness of the material can be further improved by adding rare earth elements, and the stability of the deposited metal can be enhanced through micro-alloying, and the best effect can be achieved within the composition range of 0.002%-0.006%.
[0053] The stainless steel welding wire of the present invention is prepared according to the following method: desulfurized molten iron is used in a converter to make steel, and raw materials such as electrolytic manganese, ferrosilicon, chromium nitride, metal nickel, metal molybdenum, copper powder, ferrovanadium, ferrotungsten, borax, potassium titanate, mixed rare earth, pure iron, etc. are added in proportion during the smelting process, and a top and bottom composite blowing process is adopted to smelt until carbon, sulfur and phosphorus are controlled at a specified level, and after deoxidation and alloying, a refining process outside the LF furnace is adopted to adjust some trace elements to smelt molten steel with components meeting the requirements, and the molten steel is cast into a continuous casting billet through a casting device, and then rolled into a wire rod with a diameter of 4 to 7 mm, and then the wire rod is drawn into a finished welding wire with a diameter of 0.5 to 2.5 mm.
[0054] Compared with the original products, the product cost of the present invention is further reduced, the welding efficiency is high, and the welding process performance is excellent. The composition ratio of the welding wire is scientific and reasonable, and the deposited metal has a considerable amount of ferrite, which disrupts the crystallization direction of the austenite structure, strengthens the grain boundary, and avoids the generation of welding hot cracks from the organizational perspective. The element ratio of the present invention improves the high-temperature oxidation resistance and high-temperature sulfide corrosion resistance of the weld metal, so that the high-temperature comprehensive performance of the deposited metal is improved, and the service life of the weldment is extended.
[0055] The welding wire obtained by the present invention has the excellent technical effects as described above and below. DETAILED DESCRIPTION
[0056] The present invention can be further described by the following examples, however, the scope of the present invention is not limited to the following examples. It will be appreciated by those skilled in the art that various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. The present invention provides general and / or specific descriptions of the materials and test methods used in the test. Although many materials and operating methods used to achieve the purpose of the present invention are well known in the art, the present invention is still described in as much detail as possible at this point.
[0057] In the following examples, when the chemical composition of the welding wire or the chemical composition of the deposited metal is shown, unless otherwise specified, each numerical value is a value of %.
[0058] Example 1: Stainless steel solid welding wire for magnesium industry equipment welding
[0059] The chemical composition of the welding wire designed in this embodiment is: C: 0.06, Mn: 2.5, Si: 0.53, P: 0.023, S: 0.009, Cr: 22.5, Ni: 7.3, Mo: 0.13, Cu: 0.13, N: 0.13, V: 0.054, W: 0.045, B: 0.012, Ti: 0.031, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.005, and the rest is Fe and other inevitable impurities.
[0060] The preparation method is as follows: desulfurized molten iron is used in a converter to make steel; during the smelting process, raw materials such as electrolytic manganese, ferrosilicon, chromium nitride, metallic nickel, metallic molybdenum, copper powder, ferrovanadium, ferrotungsten, borax, potassium titanate, mixed rare earth, pure iron, etc. are added in proportion; a top and bottom composite blowing process is used to smelt until carbon, sulfur and phosphorus are controlled at specified levels; after deoxidation and alloying, an LF furnace off-furnace refining process is used to adjust some trace elements to smelt molten steel with components meeting the requirements; the molten steel is cast into a continuous casting billet through a casting device, and then rolled into a wire rod with a diameter of Φ=5.5 mm; then the wire rod is drawn into a finished welding wire with a diameter of Φ=1.2 mm.
[0061] Use metal arc welding (current: 120-160A, shielding gas: 80% Ar + 20% CO 2 ) was welded, and the chemical composition of the deposited metal was C: 0.05, Mn: 2.4, Si: 0.51, P: 0.024, S: 0.010, Cr: 22.1, Ni: 7.2, Mo: 0.11, Cu: 0.12, N: 0.10, V: 0.049, W: 0.043, B: 0.011, Ti: 0.023, RE (mixed rare earth): 0.004, and the rest was Fe and other inevitable impurities.
[0062] The above-mentioned metal-electrode gas shielded welding is performed on the steel used for magnesium equipment (ZG3Cr24Ni7NRE, a typical steel for magnesium reduction tanks). The welding process performance is good, and no welding cracks occur. The welded joint formed has excellent high-temperature creep resistance and meets actual production needs. Its service life is more than 130 days (137 days in this example), which is about 20% or more higher than the general service life of the prior art (usually 80 to 100 days).
[0063] Example 2: Stainless steel solid welding wire for magnesium industry equipment welding
[0064] The chemical composition of the welding wire designed in this embodiment is: C: 0.10, Mn: 1.2, Si: 0.36, P: 0.019, S: 0.012, Cr: 23.9, Ni: 7.9, Mo: 0.11, Cu: 0.12, N: 0.09, V: 0.073, W: 0.049, B: 0.014, Ti: 0.029, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.004, and the rest is Fe and other inevitable impurities.
[0065] The welding wire was prepared according to the method of Example 1.
[0066] Use metal arc welding (current: 120-160A, shielding gas: 80% Ar + 20% CO 2 ) was welded, and the chemical composition of the deposited metal was C: 0.09, Mn: 1.1, Si: 0.30, P: 0.019, S: 0.013, Cr: 23.5, Ni: 7.5, Mo: 0.10, Cu: 0.12, N: 0.08, V: 0.067, W: 0.048, B: 0.013, Ti: 0.020, RE (mixed rare earth): 0.003, and the rest was Fe and other inevitable impurities.
[0067] The above-mentioned metal-arc gas shielded welding is performed on the steel used for magnesium equipment (ZG3Cr24Ni7NRE, a typical steel for magnesium reduction tanks). The welding process performance is good, and no welding cracks occur. The welded joints formed have excellent high-temperature creep resistance and meet actual production needs. The service life is more than 130 days (136 days in this example), which is about 20% or more higher than the general service life of the prior art (usually 80 to 100 days).
[0068] Example 3: Stainless steel solid welding wire for magnesium industry equipment welding
[0069] The chemical composition of the welding wire designed in this embodiment is: C: 0.24, Mn: 2.9, Si: 0.63, P: 0.026, S: 0.011, Cr: 21.9, Ni: 8.5, Mo: 0.07, Cu: 0.12, N: 0.22, V: 0.064, W: 0.023, B: 0.019, Ti: 0.046, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.005, and the rest is Fe and other inevitable impurities.
[0070] The welding wire was prepared according to the method of Example 1.
[0071] Use metal arc welding (current: 120-160A, shielding gas: 80% Ar + 20% CO2) for welding, and the chemical composition of the deposited metal is C: 0.23, Mn: 2.5, Si: 0.52, P: 0.025, S: 0.010, Cr: 21.1, Ni: 8.3, Mo: 0.06, Cu: 0.12, N: 0.21, V: 0.059, W: 0.021, B: 0.017, Ti: 0.042, RE (mixed rare earth): 0.004, and the rest is Fe and other inevitable impurities.
[0072] The above-mentioned metal-electrode gas shielded welding is performed on the steel used for magnesium equipment (ZG3Cr24Ni7NRE, a typical steel for magnesium reduction tanks). The welding process performance is good, and no welding cracks occur. The welded joints formed have excellent high-temperature creep resistance and meet actual production needs. The service life is more than 130 days (132 days in this example), which is about 20% or more higher than the general service life of the prior art (usually 80 to 100 days).
[0073] Example 4: Stainless steel solid welding wire for magnesium industry equipment welding
[0074] The chemical composition of the welding wire designed in this embodiment is: C: 0.28, Mn: 1.6, Si: 0.29, P: 0.021, S: 0.008, Cr: 24.8, Ni: 8.8, Mo: 0.09, Cu: 0.11, N: 0.27, V: 0.082, W: 0.037, B: 0.016, Ti: 0.031, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.003, and the rest is Fe and other inevitable impurities.
[0075] The welding wire was prepared according to the method of Example 1.
[0076] Use metal arc welding (current: 120-160A, shielding gas: 80% Ar + 20% CO2) for welding, and the chemical composition of the deposited metal is C: 0.25, Mn: 1.4, Si: 0.26, P: 0.021, S: 0.007, Cr: 24.2, Ni: 8.3, Mo: 0.07, Cu: 0.11, N: 0.26, V: 0.076, W: 0.033, B: 0.013, Ti: 0.025, RE (mixed rare earth): 0.002, and the rest is Fe and other inevitable impurities.
[0077] The above-mentioned metal-electrode gas shielded welding is performed on the steel used for magnesium equipment (ZG3Cr24Ni7NRE, a typical steel for magnesium reduction tanks). The welding process performance is good, and no welding cracks occur. The welded joint formed has excellent high-temperature creep resistance and meets actual production needs. Its service life is more than 130 days (138 days in this example), which is about 20% or more higher than the general service life of the prior art (usually 80 to 100 days).
[0078] Example 5: Stainless steel solid welding wire for magnesium industry equipment welding
[0079] The chemical composition of the welding wire designed in this embodiment is: C: 0.17, Mn: 2.2, Si: 0.44, P: 0.019, S: 0.009, Cr: 23.3, Ni: 9.6, Mo: 0.14, Cu: 0.13, N: 0.17, V: 0.084, W: 0.056, B: 0.015, Ti: 0.034, RE (mixed rare earth La: Ce: Nd = 2: 5: 1): 0.004, and the rest is Fe and other inevitable impurities.
[0080] The welding wire was prepared according to the method of Example 1.
[0081] Using metal arc welding (current: 120-160A, shielding gas: 80% Ar + 20% CO2) for welding, the chemical composition of the deposited metal is C: 0.12, Mn: 2.0, Si: 0.37, P: 0.018, S: 0.009, Cr: 23.0, Ni: 9.3, Mo: 0.12, Cu: 0.11, N: 0.14, V: 0.074, W: 0.053, B: 0.013, Ti: 0.031, RE (mixed rare earth): 0.003, and the rest is Fe and other inevitable impurities.
[0082] The above-mentioned metal-arc gas shielded welding is performed on the steel used for magnesium equipment (ZG3Cr24Ni7NRE, a typical steel for magnesium reduction tanks). The welding process performance is good, and no welding cracks occur. The welded joints formed have excellent high-temperature creep resistance and meet actual production needs. The service life is more than 130 days (134 days in this example), which is about 20% or more higher than the general service life of the prior art (usually 80 to 100 days).
[0083] Comparative Example 1: A welding material for magnesium industry was prepared according to the ingredients and method of Example 1 in the specification of CN101362260B.
[0084] Comparative Example 2: A welding material for magnesium industry was prepared according to the ingredients and method of Example 2 in the specification of CN101362260B.
[0085] Comparative Example 3: A welding material for magnesium industry was prepared according to the ingredients and method of Example 3 in the specification of CN101362260B.
[0086] Comparative Example 4: A welding material for magnesium industry was prepared according to the ingredients and method of Example 4 in the specification of CN101362260B.
[0087] Comparative Example 5: A welding material for magnesium industry was prepared according to the ingredients and method of Example 5 in the specification of CN101362260B.
[0088] Test Example 1: Investigation of the deposited metal's resistance to high-temperature sulfidation corrosion and high-temperature oxidation
[0089] Test method: To simulate the working conditions of the equipment, high-temperature oxidation test at 1250℃h and high-temperature sulfidation corrosion test at 1200℃ were carried out. After the high-temperature test, the samples were weighed by discontinuous weighing method after heating for different times, and the weight loss rate of the samples was calculated: weight loss rate = weight loss / sample surface area.
[0090] Using the welding materials obtained in the above Examples 1-5 and Comparative Examples 1-5, welding was performed using the method of Example 1 with ZG3Cr24Ni7NRE base material, a typical steel used for magnesium reduction tanks, to obtain deposited metal as a corrosion sample with a size of 100 mm×50 mm×50 mm.
[0091] After the corrosion samples were heated at 1250℃ for 50h, their high temperature oxidation resistance was measured. After being heated at 1200℃ in a sulfur-containing atmosphere for 10h, their high temperature sulfidation resistance was measured. The weight loss rate was used to characterize their high temperature oxidation / sulfidation resistance. The results showed that the high temperature sulfidation corrosion resistance and high temperature oxidation resistance of the deposited metal of the product of the present invention were significantly improved. The specific results are shown in Table 1 and Table 2.
[0092] Table 1: Weight loss rate of examples, g / m 2
[0093] project Example 1 Example 2 Example 3 Example 4 Example 5 High temperature oxidation resistance 248.6 227.4 238.6 214.2 213.1 High temperature vulcanization resistance 17.3 20.4 13.8 12.1 13.7
[0094] Table 2: Weight loss rate of comparative samples, g / m 2
[0095] project Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 High temperature oxidation resistance 314.4 324.5 383.7 301.2 342.1 High temperature vulcanization resistance 173.2 173.2 142.0 100.4 123.6
[0096] In addition, the inventors have also found in some supplementary tests that the combined addition of V, W and B has a significant effect on improving the high temperature oxidation resistance and high temperature sulfidation resistance of the welding wires of Examples 1 to 5. The specific supplementary tests are as follows. Supplementary test a, referring to Examples 1 to 5 but without adding V, 5 kinds of welding wires were obtained, they were welded according to the method of Example 1, and the weight loss rate of each corrosion sample was measured according to Test Example 1. The weight loss rate of high temperature oxidation resistance was 293-314 g / m 2 For example, the weight loss rate of the corrosion sample of the welding wire obtained in Example 1 is 298.5 g / m 2 The weight loss rate of high temperature vulcanization resistance is between 112 and 164 g / m 2 For example, the weight loss rate of the corrosion sample of the welding wire obtained in Example 1 is 137.4 g / m 2 In supplementary test b, five kinds of welding wires were obtained by referring to Examples 1 to 5 but without adding W. They were welded according to the method of Example 1, and the weight loss rate of each corrosion sample was measured according to Test Example 1. The weight loss rate of high temperature oxidation resistance was 286-319 g / m 2 For example, the weight loss rate of the corrosion sample of the welding wire obtained in Example 1 is 303.7 g / m 2 The weight loss rate of high temperature vulcanization resistance is between 103 and 147 g / m 2 For example, the weight loss rate of the corrosion sample of the welding wire obtained in Example 1 is 126.2 g / m 2 In supplementary test c, five kinds of welding wires were obtained by referring to Examples 1 to 5 but without adding B. They were welded according to the method of Example 1, and the weight loss rate of each corrosion sample was measured according to Test Example 1. The weight loss rate of high temperature oxidation resistance was 298 to 344 g / m 2For example, the weight loss rate of the corrosion sample of the welding wire obtained in Example 1 is 311.2 g / m 2 The weight loss rate of high temperature vulcanization resistance is between 108 and 142 g / m 2 For example, the weight loss rate of the corrosion sample of the welding wire obtained in Example 1 is 119.7 g / m 2 In supplementary test d, five welding wires were obtained by referring to Examples 1 to 5 but without adding V and W, or by not adding V and B, or by not adding W and B. They were welded according to the method of Example 1, and the weight loss rate of each corrosion sample was measured according to Test Example 1. The weight loss rate of high temperature oxidation resistance was 291 to 336 g / m 2 For example, the weight loss rate of the corrosion sample of the welding wire without adding V and W obtained in Example 1 is 322.7g / m 2 The weight loss rate of high temperature vulcanization resistance is between 102 and 137 g / m 2 For example, the weight loss rate of the corrosion sample of the welding wire without adding V and W obtained in Example 1 is 118.3 g / m 2 The welding wire obtained by combining V, W and B gives the deposited metal excellent corrosion resistance, which is completely unforeseeable in the prior art.
[0097] Different from the prior art, the solid welding wire of the present invention can be used in automated welding processes due to the excellent uniformity of the internal and external materials, while other types of welding materials can only be welded manually, or although they can be welded automatically, the work efficiency and welding quality are far inferior to those of solid welding wire.
[0098] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A stainless steel solid welding wire, characterized in that: Its chemical composition mass percentage is: C: 0.28%, Mn: 1.6%, Si: 0.29%, P: 0.021%, S: 0.008%, Cr: 24.8%, Ni: 8.8%, Mo: 0.09%, Cu: 0.11%, N: 0.27%, V: 0.082%, W: 0.037%, B: 0.016%, Ti: 0.031%, RE: 0.003%, the rest is Fe and other unavoidable impurities; wherein, the RE, i.e., mixed rare earth, is a mixed rare earth with La:Ce:Nd in a weight ratio of 2:5:1; the welding wire is prepared according to the following method: using desulfurized hot metal converter to make steel, adding raw materials such as electrolytic manganese, ferrosilicon, chromium nitride, metal nickel, metal molybdenum, copper powder, ferrovanadium, ferrotungsten, borax, potassium titanate, mixed rare earth, and pure iron in a proportional ratio during the smelting process, and using a top and bottom composite blowing process to smelt until carbon, sulfur, and phosphorus are controlled at a specified level, and then After deoxidation and alloying, the LF furnace's off-furnace refining process is used to adjust some trace elements and smelt molten steel with the required composition. The molten steel is cast into continuous casting billets through casting equipment, and then rolled into wire rods with a diameter of Φ = 4~7mm. The wire rods are then drawn into finished welding wires with a diameter of Φ = 0.5~2.5mm. The welding wire is welded using a metal arc welding method with a current of 120-160A and a shielding gas of 80% Ar + 20% CO2 to obtain the chemical composition of the deposited metal. The mass percentages are: C: 0.25%, Mn: 1.4%, Si: 0.26%, P: 0.021%, S: 0.007%, Cr: 24.2%, Ni: 8.3%, Mo: 0.07%, Cu: 0.11%, N: 0.26%, V: 0.076%, W: 0.033%, B: 0.013%, Ti: 0.025%, RE: 0.002%, and the rest are Fe and other unavoidable impurities.
2. A stainless steel solid welding wire, characterized in that: Its chemical composition mass percentage is: C: 0.17%, Mn: 2.2%, Si: 0.44%, P: 0.019%, S: 0.009%, Cr: 23.3%, Ni: 9.6%, Mo: 0.14%, Cu: 0.13%, N: 0.17%, V: 0.084%, W: 0.056%, B: 0.015%, Ti: 0.034%, RE: 0.004%, the rest is Fe and other unavoidable impurities; wherein, the RE, i.e., mixed rare earth, is a mixed rare earth with La:Ce:Nd in a weight ratio of 2:5:1; the welding wire is prepared according to the following method: using desulfurized hot metal converter to make steel, adding raw materials such as electrolytic manganese, ferrosilicon, chromium nitride, metal nickel, metal molybdenum, copper powder, ferrovanadium, ferrotungsten, borax, potassium titanate, mixed rare earth, and pure iron in a proportional ratio during the smelting process, and using a top and bottom composite blowing process to smelt until carbon, sulfur, and phosphorus are controlled at a specified level, After deoxidation and alloying, the LF furnace's off-furnace refining process is used to adjust some trace elements and smelt molten steel with the required composition. The molten steel is cast into continuous casting billets through casting equipment, and then rolled into wire rods with a diameter of Φ = 4~7mm. The wire rods are then drawn into finished welding wires with a diameter of Φ = 0.5~2.5mm. The welding wire is welded using a metal arc welding method with a current of 120-160A and a shielding gas of 80% Ar + 20% CO2 to obtain the chemical composition of the deposited metal. The mass percentages are: C: 0.12%, Mn: 2.0%, Si: 0.37%, P: 0.018%, S: 0.009%, Cr: 23.0%, Ni: 9.3%, Mo: 0.12%, Cu: 0.11%, N: 0.14%, V: 0.074%, W: 0.053%, B: 0.013%, Ti: 0.031%, RE: 0.003%, and the rest are Fe and other unavoidable impurities.
3. The method for preparing the stainless steel solid welding wire according to claim 1 comprises the following steps: using desulfurized molten iron in a converter to make steel, adding raw materials such as electrolytic manganese, ferrosilicon, chromium nitride, metallic nickel, metallic molybdenum, copper powder, ferrovanadium, ferrotungsten, borax, potassium titanate, mixed rare earth and pure iron in a proportioned manner during the smelting process, adopting a top and bottom composite blowing process to smelt until carbon, sulfur and phosphorus are controlled at a specified level, after deoxidation and alloying, adopting an LF furnace off-furnace refining process to adjust some trace elements, and smelting molten steel with a composition that meets the requirements, casting the molten steel into a continuous casting billet through a casting equipment, and then rolling it into a wire rod with a diameter of Φ = 4 to 7 mm, and then drawing the wire rod into a finished welding wire with a diameter of Φ = 0.5 to 2.5 mm.
4. The method for preparing the stainless steel solid welding wire according to claim 2 comprises the following steps: using desulfurized molten iron in a converter to make steel, adding raw materials such as electrolytic manganese, ferrosilicon, chromium nitride, metallic nickel, metallic molybdenum, copper powder, ferrovanadium, ferrotungsten, borax, potassium titanate, mixed rare earth and pure iron in a proportioned manner during the smelting process, adopting a top and bottom composite blowing process to smelt until carbon, sulfur and phosphorus are controlled at a specified level, after deoxidation and alloying, adopting an LF furnace off-furnace refining process to adjust some trace elements, and smelting molten steel with a composition that meets the requirements, casting the molten steel into a continuous casting billet through a casting equipment, and then rolling it into a wire rod with a diameter of Φ = 4 to 7 mm, and then drawing the wire rod into a finished welding wire with a diameter of Φ = 0.5 to 2.5 mm.
Citation Information
Patent Citations
Stainless steel electrode special for magnesium reduction pot
CN101362260B
Submerged arc welding wire for stainless steel
CN101352786A
High-temperature wear-resistant surfacing alloy material based on ultralow-carbon high-boron and preparation method and application thereof
CN108817730A
Welding wire for stainless steel welding
CN110919235A
Welding rod for welding magnesium smelting reduction tank and preparation method of welding rod
CN115971722A